2015
DOI: 10.1111/spc3.12185
|View full text |Cite
|
Sign up to set email alerts
|

A Big Tent of Dark Personality Traits

Abstract: Researchers have become very interested in socially aversive personality traits in recent years as ref lected by the considerable number of publications concerning the Dark Triad of personality (i.e., Machiavellianism, narcissism, and psychopathy). The goal of the present article is to suggest that researchers broaden their view of potentially dark personality features. We provide overviews of two dark personality features that have been largely neglected by psychologists (i.e., spitefulness and greed) and poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(62 citation statements)
references
References 81 publications
(88 reference statements)
3
58
0
1
Order By: Relevance
“…Future researchers may wish to study narcissism-aggression links in broader socially dynamic contexts, including not only dyads, but also small groups (Campbell, Bush, Brunell, & Shelton, 2005). Researchers may also wish to consider casting a wider net of dark personality traits to include sadism (Buckels, Jones, & Paulhus, 2013;Charbol, Van Leeuwen, Rodgers, & Séjourné, 2009) or greed and spitefulness (Marcus & Zeigler-Hill, 2015).…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…Future researchers may wish to study narcissism-aggression links in broader socially dynamic contexts, including not only dyads, but also small groups (Campbell, Bush, Brunell, & Shelton, 2005). Researchers may also wish to consider casting a wider net of dark personality traits to include sadism (Buckels, Jones, & Paulhus, 2013;Charbol, Van Leeuwen, Rodgers, & Séjourné, 2009) or greed and spitefulness (Marcus & Zeigler-Hill, 2015).…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…A recent meta-analysis exploring the DT and the BFF has questioned the distinction between psychopathy and Machiavellianism, encouraging researchers to explore the convergent validity between these two constructs (O'Boyle et al, 2015;Vize et al, 2018), and called for better measurement, more rigorous methodology, and increased usage to achieve a more accurate picture of the construct's validity. Marcus and Zeigler-Hill (2015) suggested that researchers broaden their views of dark traits and proposed the existence of a "dark tent," which includes other antisocial behaviors such as spitefulness and greed. In reviewing other research that extended the DT cross-culturally, we failed to observe any disclosure of structural invariance testing (see Jonason et al, 2013Jonason et al, , 2017, or those that did reported barely "acceptable" fits (Robertson et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There have been some attempts made to expand the traits to include everyday sadistic tendencies (Buckels, Jones, & Paulhus, 2013) and spitefulness (Marcus & Zeigler-Hill, 2015). One issue centers around the question of sufficiency.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…In line with the lower-level facet measurement criticisms is the question of whether the three traits are enough to capture the dark side of human nature. There have been some attempts made to expand the traits to include everyday sadistic tendencies (Buckels, Jones, & Paulhus, 2013) and spitefulness (Marcus & Zeigler-Hill, 2015). While interesting to consider, there is substantial overlap for sadism and spitefulness with psychopathy, making them difficult to disentangle (Bertl et al, 2017;Jonason, Zeigler-Hill, & Okan, 2017).…”
Section: Future Directions and Conclusionmentioning
confidence: 99%